ANALISIS STRATEGI DIGITAL MARKETING TOKO SEPATU FEBYOLA SHOES DI BETENG TRADE CENTER SURAKARTA - Nur Muftiyanto, R. Taufiq; Purnomo, Singgih (JURNAL ILMIAH EDUNOMIKA, 2022)
The rapid spread of the COVID-19 pandemic in Indonesia has indeed changed the interaction between businesses and customers, forcing the Febyola Shoes Store at Beteng Trade Center Surakarta to change its marketing pattern from conventional offline marketing to online marketing. This research was conducted in order to help optimize the digital marketing strategy implemented to be more efficient and targeted. The research uses a qualitative descriptive approach with the External and Internal Environmental Analysis Method and SWOT. It is known that the use of online shopping services shows that before the pandemic, 60.3% of young people stated that they had never shopped online or only around 39.7% had shopped online. However, after the pandemic hit, survey data showed that 100% of young people had shopped online. The survey results show that Whatsapp is the favorite social media for internet users worldwide with a percentage of 24.1% of respondents liking Whatsapp compared to other platforms, beating Facebook with 21.8%, Instagram 18.4%, and other media that are far behind the three most popular media at this time. The company uses Instagram social media as a Digital Marketing Media but is not optimal. There are obstacles in the Company's Digital Marketing activities, namely the promotion carried out is not right on target and the promotional strategy is still inconsistent. There is a great opportunity for a wider market potential than before at a low cost using Digital Marketing. Keywords: Digital Marketing Strategy, SWOT Analysis, Internal-External Factors, Internal-External Matrix